Computed tomography-based diagnosis of occult fragility hip fractures offer shorter waiting times with no inadvertent missed diagnosis. (16th June 2020) - Law, Gin Way; Padki, Akshay; Tay, Kae Sian; Howe, Tet Sen; Koh, Joyce Suang Bee; Mak, May San; Mohan, P Chandra; Chan, Lai Peng; Png, Meng Ai
Purpose: Surgical delay due to the wait for advanced cross-sectional imaging in occult fragility hip fracture management is not well studied. Our study aims to investigate computed tomography (CT) as an alternative to the gold standard magnetic resonance imaging (MRI) in occult hip fracture workup to decrease surgical delay. Methods: We conducted a retrospective review of all CTs and MRIs performed between 2015 and 2017 for patients with clinically suspected fragility hip fractures and negative plain radiographs to investigate surgical delay resulting from the wait for advanced imaging and representations due to missed fractures. Results: A total of 243 scans (42 CTs and 201 MRIs) were performed for occult hip fracture workup over the study timeframe, of which 49 patients (20%) had occult hip fractures [CT: 6 (14%), MRI: 43 (21%), p = 0.296)]. There were no readmissions for fracture in the 12 months following a negative scan. The CT group had shorter waiting times (CT: 29 ± 24 h, MRI: 44 ± 32 h, p = 0.004) without significantly reducing surgical delay (CT: 82 ± 36 h, MRI: 128 ± 58 h, p = 0.196). The MRI group had a higher number of patients with a cancer history ( p = 0.036), reflective of the practice for workup of possible metastases as a secondary intention. Conclusion: Advanced cross-sectional imaging wait times in occult hip fracture workup contribute significantly to surgical delay. Modern CT techniques are not inferior to MRI in detecting occult fractures and may be a suitable alternative in the absence of a cancer history if MRI cannot be obtained in a timely fashion or is contraindicated. Clinicians should utilize the more readily available imaging modality to reduce surgical delay.